Portraits - Kruk, Liedeke (Amsterdam : Stichting Roma Publications, 2011)
Summary: In this book Liedeke Kruk is an artist dedicated to the photographic capture of other artists. The portraits here are varied; intimate and distant, clear and indistinct, relaxed and tense, good humoured and grumpy. But the overall effect of this portfolio is remarkable, with page after page of contemporary art's big hitters unfolding before the eyes, including shots of Luc Tuymans, Marlene Dumas, Gillian Wearing, Tacita Dean, Karel Appel, Jeff Wall, Pipilotti Rist, Sigmar Polke, Thomas Struth, Mike Kelley, Dan Graham, Bill Viola, Sophie Calle, and dozens more. This book contains more than 200 portraits and artists, which are made between 1993 and 2010.
boek
Keywords: Kruk, Liedeke